2007
DOI: 10.1038/sj.ijo.0803741
|View full text |Cite
|
Sign up to set email alerts
|

Maternal adiposity prior to pregnancy is associated with ADHD symptoms in offspring: evidence from three prospective pregnancy cohorts

Abstract: Objectives: We examine whether pregnancy weight (pre-pregnancy body mass index (BMI) and/or weight gain) is related to core symptoms of attention deficit hyperactivity disorder (ADHD) in school-age offspring. Design: Follow-up of prospective pregnancy cohorts from Sweden, Denmark and Finland within the Nordic Network on ADHD. Methods: Maternal pregnancy and delivery data were collected prospectively. Teachers rated inattention and hyperactivity symptoms in offspring. High scores were defined as at least one co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
221
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(236 citation statements)
references
References 43 publications
11
221
1
3
Order By: Relevance
“…Associations have been reported between prepregnancy obesity and intellectual disability, 12,16 lower cognitive performance, 10,13,14,17,21 ADHD, 11,19,20,32 and autism 15 in children. One null study was also reported; however, it was limited by assessing all overweight and obese women as a single group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations have been reported between prepregnancy obesity and intellectual disability, 12,16 lower cognitive performance, 10,13,14,17,21 ADHD, 11,19,20,32 and autism 15 in children. One null study was also reported; however, it was limited by assessing all overweight and obese women as a single group.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Recent epidemiologic studies suggest associations between prepregnancy obesity and various neurodevelopmental outcomes. [10][11][12][13][14][15][16][17][18][19][20][21] However, these studies were limited by small sample sizes, insufficient information on confounders and mediators, and imprecise neurodevelopment measures. Additionally, 1 study reported no association.…”
Section: What This Study Addsmentioning
confidence: 99%
“…This has been little explored in humans beyond childhood. However, there is emerging evidence that maternal obesity impacts on offspring brain function including cognitive function and psychiatric or mood disturbances; children of women who are overweight pre-pregnancy or gain a large amount of weight during pregnancy have a twofold risk of attention deficit hyperactivity disorder symptoms compared to normalweight women (Rodriguez et al 2008), as well as problems with emotional regulation (Rodriguez 2010). These effects are substantial, and thus clinically relevant, if causal.…”
Section: Other Programming Targetsmentioning
confidence: 99%
“…There is some evidence that suggests that mothers who have studied more have a better physical and temporal environmental organization, more opportunities to vary daily stimulation with different availability of tools and games more suitable for their toddlers and greater emotional and verbal link [23]. However, less schooling is an important SES marker.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer frequent studies that include other pre-partum mental disorders [12][13][14][15], as well as important environmental stressors, as violence. Yet these conditions are highly prevalent in developing countries and in deprived areas of wealthier nations [16][17][18][19][20][21][22][23][24]. In addition to this, most evidence comes from studies that were carried in clinical settings, lacking data on populationbased samples [12]; developmental assessment in epidemiological studies are seldom done through more sophisticated tests that requires trained professionals [3,8]; finally the identification of effect-modifiers (interaction) in these association has been acknowledge as necessary [25].…”
Section: Introductionmentioning
confidence: 99%